Cover crop management in the vineyards of the Lower Orange River region, South Africa: 1. Performance of grass and broadleaf species - Fourie, J.C. (South African Journal of Enology and Viticulture, 2017)
This trial was conducted over a period of four years on a sandy soil in a Sultanina vineyard on own roots in Keimoes (28o40’S, 20o54’E), situated in the semi-arid Lower Orange River region. Eighteen treatments, consisting of three cover crop management practices applied selectively to ten cover crop species, as well as two treatments in which the weeds were managed in accordance with two management practices generally applied by producers in the region, were applied. The average dry matter production (DMP) of the cover crop species sown annually (SA) and controlled chemically before bud break (BB), as determined during bud break (beginning of August) was: Medicago truncatula Gaertn. v. Paraggio > Vicia dasycarpa Ten. (grazing vetch) > Secale cereale L. v. Henog (rye) > Ornithopus sativus L. v. Emena > Avena sativa L. v. Overberg > Lolium multiflorum Lam. v. Midmar (‘Midmar’ ryegrass) > Avena strigosa L. v. Saia (‘Saia’ oats) > Trifolium subterraneum L. v. Woogenellup. ‘Midmar’ ryegrass and grazing vetch re-established successfully. Winter growing weeds were effectively suppressed (weed stand less than 10% of that of the control) by rye (BB/SA) and ‘Saia’ oats (BB/SA) for the duration of the trial. Weed growth from véraison to harvest (mid-November to the end of December) was effectively reduced in all the annual cover crop treatments compared with the treatment in which the weeds were controlled mechanically from bud break during the 1997/98 season. Festuca arundinaceae L. v. Cochise, slashed regularly throughout the season, suppressed the winter and summer growing weeds effectively during the trial, but eventually got infested with common couch.